O Plano Marshall: Uma abordagem atual à formulaç\~ao, ao desenho e à coordenaç\~ao de políticas públicas e programas governamentais - Antônio Lassance (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– This working paper investigates the Marshall Plan from an unprecedented angle: that of strategy formulation, policy design, and the coordination of policy implementation. Through an in-depth case study, the Marshall Plan proves to be a far-reaching experience that still brings to light chronic and crucial problems for those interested in ex ante policy analysis. The conclusion is that the plan can be reinterpreted as an approach to complex and multi-causal problems (wicked problems) in search of building integrated solutions and government action as coordinated as possible. The approach consists of striving for strategic definitions centered on the correct choice of priority problems and the identification of their causal chain. Around these definitions, the policy design seeks to balance short-term responses with attention to long-term causes. Such assumptions precede issues such as, for example, the efficient budget allocation and the optimization of administrative and regulatory resources - concerns which are more focused on consequences than on root causes. With these preliminaries guaranteed, the policy design establishes a policy governance with due command and central control over the strategy, but with managerial autonomy over the programs. It leaves an open part of the process of formulating alternatives so that they adjust to a decentralized and capillarized implementation, with a technical cooperation network that remains close to the street-level bureaucracy.
Keywords: H11; D04; B15; 330; Marshall Plan; policy design; ex ante analysis of public policies; economic history; political economy